Effect of agmatine on L-type calcium current in rat ventricular myocytes. - LI Qing; YIN Jing-Xiang; HE Rui-Rong (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of agmatine (Agm) on L-type calcium current (I(Ca-L)) in rat ventricular myocytes. METHODS: Whole-cell configuration of the patch-clamp technique was used to record I(Ca-L) in single rat ventricular myocytes which were dissociated by enzymatic dissociation method. RESULTS: (1) Agm (0.5, 1, 2 mmol/L) reduced the voltage-dependently activated peak amplitude of I(Ca-L) (pA) from 1451+/-236 (control) to 937+/-105 (n=8, P